The effect of fibre content on the split tensile strength of sago fibre reinforced concrete - Wong, Sia Siang (Universiti Malaysia Sarawak (UNIMAS), 2017)
Sago fibre is one of the major constituents found in sago pith waste after the processing of sago starch. The previous studies done by various researchers had identified that the addition of fibre in concrete could enhance the tensile strength development in concrete inherently by the bridging effect of fibre. However, there is still lack of study on sago fibre reinforced concrete. Therefore, this research is conducted to investigate the effect of fibre content towards tensile strength development in sago fibre reinforced concrete. It is vital to ensure the feasibility of application of sago fibre reinforced concrete in actual practice. In this research, the sago fibre applied is 30mm in length and the percentages of fibre added are 0.5%, 1.0%, 1.5%, and 2.0% by concrete volume respectively. The results of these fibre contents are compared with the control sample (0% fibre content) at curing ages of 3, 7, 28, and 56 days. The test for workability of fresh concrete involved slump test, while the strength properties of hardened concrete is tested by compressive and split tensile strength tests. In general, the workability of concrete decreased with the increment of sago fibre content. Besides that, the compressive strength developed in sago fibre reinforced concrete is higher than the control sample during the early ages, but declined at later ages. Meanwhile, the tensile strength of sago fibre reinforced concrete is improved for lower sago fibre content of 0.5% and 1.0%, but reduced for further increment in fibre content at 1.5% and 2.0%. Therefore, the addition of 1.0% of sago fibre in concrete is believed to give the most enhancement in tensile properties of concrete